Sextortion (Fenomena Pemerasan Seksual di Lingkungan Pendidikan) - Amalia Syauket; Ika Dewi Sartika Saimima; Rajanner P Simarmata; Widya Romasindah Aidy; Nina Zainab; Rahadi Budi Prayitno; Cornelia Evelin Cabui (Jurnal Kajian Ilmiah, 2022)
There seems to be something different from the results of Transparency International Indonesia (TII) including sextortion or sexual extortion in the Global Corruption Barometer Asia 2020. This is extortion in the form of violence or sexual harassment. Generally a form of abuse of power. Sextortion is different from the corruption we know in a legal context. In terms of regulations and institutions, the practice of sextortion or sextortion is a case that occurs quite a lot but is not yet known in corruption eradication institutions in Indonesia. Sextortion is a new area that opens everyone's eyes to the fact that corruption is not only about money. This study uses a qualitative approach to answer how the form of legal protection for victims of sextortion is rife lately in the educational environment. The conclusions of this study indicate that the form of legal protection for victims of sextortion in the educational environment is in the form of assistance, protection and recovery of victims by strengthening the legal aspect in the form of SOPs for Handling Sexual Violence in each educational institution as well as the installation of detection devices. The novelty of this research can be used for extensive interpretation of legal findings by judges to protect victims of sextortion. And the importance of education on strong self-protection awareness, boldly rejecting or saying no.